Kajian Morfologi, Sitologi, dan Struktur Anatomi Daun Nepenthes spp. asal Kalimantan Barat - DAMAYANTI, FITRI; ROOSTIKA, IKA; MANSUR, MUHAMMAD (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2015)
The objective was to describe morphology, structure of anatomy, and cytology characters of the five species as well as to determine their differences each other. In the present study five Nepenthes from West Kalimantan were evaluated: N. veitchii, N. negleta, N. bicalcarata, N. clipeata, and N. hirsuta. Morfology analysis of five species Nepenthes showed different morphology in particular shape of pitcher that each species have a unique pitcher. Cytology analysis showed high variation between species. In general, it was demonstrated that N. bicalcarata tended to have bigger epidermal cells and stomata. N. bicalcarata had aktinocytik tipe of stomata and N. clipeata, N. veitchii, N. hirsuta, and N. negleta had anomocytik tipe of stomata. Stomata only had on the lower surface except N. negleta had stomata on the upper too. N. negleta had the higher of density and index stomata. The result of transversal showed variation of mesofil tissue (parenchim of palisade and spons). Epidermis cell was conducted in one layer with hipoepidermis cell more than one layer with the biggest size than epidermis cell. N. veitchii had more tricoma from the others species.